2016
DOI: 10.1158/1055-9965.epi-15-1040
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use and Survival with Early-Stage Hepatocellular Carcinoma

Abstract: Background: Limited clinical and epidemiologic data suggest that statins may improve the outcomes of hepatocellular carcinoma (HCC), which has poor prognosis.Methods: We identified 1,036 stage I or II HCC patients, diagnosed between 2007 and 2009, through the linked Surveillance, Epidemiology, and End Results (SEER) Program and Medicare claims database. Of these, 363 patients were using statin either at the time of their HCC diagnosis or afterwards. We conducted multivariable Cox regression analysis to estimat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…46 Immortal time bias occurs when there is a length of time between the start of follow-up and a subsequent start of statin therapy, which is counted in the total follow-up time for a participant—but during which the participant is actually unexposed—and, thus, it seems that this participant has survived longer than a control (nonstatin user). Jeon et al 47 show how this bias can spuriously create an association by using studies of patients with liver cancer in which the OS HR for statin use versus nonuse was 0.84 ( P = .047) before and 0.98 ( P = .82) after allowance for this bias. Randomized controlled trials, such as LUNGSTAR, avoid these issues.…”
Section: Discussionmentioning
confidence: 99%
“…46 Immortal time bias occurs when there is a length of time between the start of follow-up and a subsequent start of statin therapy, which is counted in the total follow-up time for a participant—but during which the participant is actually unexposed—and, thus, it seems that this participant has survived longer than a control (nonstatin user). Jeon et al 47 show how this bias can spuriously create an association by using studies of patients with liver cancer in which the OS HR for statin use versus nonuse was 0.84 ( P = .047) before and 0.98 ( P = .82) after allowance for this bias. Randomized controlled trials, such as LUNGSTAR, avoid these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 22 were further excluded because six studies did not include HCC patients, four studies did not valuate statin use as exposure, seven studies did not evaluate mortality or recurrence outcomes in HCC patients, two studies did not contain available data for the multivariate adjusted association between statin use and clinical outcomes in HCC patients, and the remaining three were abstracts of already included studies. Finally, nine studies were included [11][12][13][14][15][16][17]25,26].…”
Section: Literature Searchmentioning
confidence: 99%
“…Since two studies reported data according to HBV infection status of the patients [11,12], and one of them also reported stratified data according to the TNM stages of the tumor [11], these datasets were included separately. Overall, nine retrospective cohort studies including 62,273 HCC patients from China [11,12,16,25], Japan [14,15], Korea [26], and the United States [13,17] were included. The mean age of the included patients varied from 54 to 67 years, with proportions of male ranging from 64% to 99%.…”
Section: Study Characteristics and Quality Evaluationmentioning
confidence: 99%
“…The data in this context are limited and controversial. While recently published findings analyzing early stage HCC patients showed no significant difference in survival related to statin treatment (20), the additional effect of statins on chemotherapy as well as transarterial chemoembolization (TACE) treatment could be beneficial in HCC patients (22).…”
mentioning
confidence: 99%